Dual Roles of Prolactin and Vasoinhibin in Inflammatory Arthritis - Clapp, Carmen; Ortiz, Georgina; García-Rodrigo, Jose F.; Ledesma-Colunga, María G.; Martínez-Díaz, Oscar F.; Adán, Norma; Martínez de la Escalera, Gonzalo (Frontiers in Endocrinology, 2022)
The term inflammatory arthritis defines a family of diseases, including rheumatoid arthritis (RA), caused by an overactive immune system, and influenced by host aspects including sex, reproductive state, and stress. Prolactin (PRL) is a sexually dimorphic, reproductive, stress-related hormone long-linked to RA under the general assumption that it aggravates the disease. However, this conclusion remains controversial since PRL has both negative and positive outcomes in RA that may depend on the hormone circulating levels, synthesis by joint tissues, and complex interactions at the inflammatory milieu. The inflamed joint is rich in matrix metalloproteases that cleave PRL to vasoinhibin, a PRL fragment with proinflammatory effects and the ability to inhibit the hyperpermeability and growth of blood vessels. This review addresses this field with the idea that explanatory mechanisms lie within the PRL/vasoinhibin axis, an integrative framework influencing not only the levels of systemic and local PRL, but also the proteolytic conversion of PRL to vasoinhibin, as vasoinhibin itself has dual actions on joint inflammation. In this review, we discuss recent findings from mouse models suggesting the upregulation of endogenous vasoinhibin by the pro-inflammatory environment and showing dichotomous actions and signaling mechanisms of PRL and vasoinhibin on joint inflammation that are cell-specific and context-dependent. We hypothesize that these opposing actions work together to balance the inflammatory response and provide new insights for understanding the pathophysiology of RA and the development of new treatments.